2020
DOI: 10.3390/molecules25143191
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview on Antioxidant Activity Determination of Silver Nanoparticles

Abstract: Our objective in this review article is to find out relevant information about methods of determination of antioxidant activity of silver nanoparticles. There are many studies dealing with mentioned problem and herein we summarize the knowledge about methods evaluating the antioxidant activity of silver nanoparticles reported so far. Many authors declare better antioxidant activity of silver nanoparticles compared to the extract used for synthesis of them. In this review, we focused on methods of antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
118
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(126 citation statements)
references
References 165 publications
(221 reference statements)
6
118
0
2
Order By: Relevance
“…The antioxidant activity of AgNPs has been studied widely 38 . In addition, it was also investigated for AgNPs prepared via biological, physical, and chemical methods 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of AgNPs has been studied widely 38 . In addition, it was also investigated for AgNPs prepared via biological, physical, and chemical methods 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Through various synthesis methods, it was possible to create nano forms with spherical, longitudinal or triangular shapes, which also effectively impairs antibacterial activity. It turned out that silver nanoparticles in the shape of trimmed triangular flakes have the strongest bactericidal and antifungal potential in dental implants [ 29 , 30 , 31 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
“…Ionic silver was replaced by nanoparticle form due to its susceptibility to complexing and precipitation. It is also suggested that AgNPs cause fewer side effects, and their safety and antibacterial potential can be further enhanced by various modifications, such as an addition of stabilizers [ 30 , 31 , 32 , 33 ]. It has also been shown that AgNPs have an inhibitory effect on various microorganisms (including Escherichia coli , Salmonella enteritidis , Listeria monocytogenes , Pseudomonas aureginosa , Staphylococcus aureus , Candida albicans ), which was determined in vitro at around 10–15 ppm [ 9 , 30 , 31 , 32 , 33 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations